2004
DOI: 10.1587/elex.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum test of a micro-solid propellant rocket array thruster

Abstract: A φ 0.8 mm micro-solid propellant rocket array thruster for simple attitude control of a 10 kg class micro-spacecraft was tested in vacuum. The micro-thruster uses boron/potassium nitrate propellant (NAB), because NAB has ignition temperature as low as 500 • C, and easily start to burn in vacuum. For a half of the rockets, an ignition aid (RK) was also loaded. Ignition was succeeded in vacuum with NAB + RK and NAB. The maximum impulse thrust of 4.6 × 10 −4 Ns, which is approximately a half of our requirement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…So far, GAP (Glycidyl Azide Polymer), lead styphnate, NAB (Boron/Potassium Nitrate B/KNO3), RK (lead rhodanide-based explosive), nitrocellulose, HMX, RDX, HTPB/AP/AL, PETN (Pentaerythritol Tetranitrate), ZPP (Zirconium Perchlorate Potassium), gun powder (KNO3/C/S/NH4ClO4/Al), DDNP (diazodinitrophenol), etc. were used and tested for micro rocket [1][2][3][4][5][6][7][8][9]. The data of these propellants are listed in Table.1.…”
Section: Propellantsmentioning
confidence: 99%
“…So far, GAP (Glycidyl Azide Polymer), lead styphnate, NAB (Boron/Potassium Nitrate B/KNO3), RK (lead rhodanide-based explosive), nitrocellulose, HMX, RDX, HTPB/AP/AL, PETN (Pentaerythritol Tetranitrate), ZPP (Zirconium Perchlorate Potassium), gun powder (KNO3/C/S/NH4ClO4/Al), DDNP (diazodinitrophenol), etc. were used and tested for micro rocket [1][2][3][4][5][6][7][8][9]. The data of these propellants are listed in Table.1.…”
Section: Propellantsmentioning
confidence: 99%
“…consisting of micronozzles and microigniters have great potential applications in the small space vehicles due to their advantages, such as having no movable components and no liquid leakage [1][2][3][4][5][6]. Especially, the MSPT array including multiple thruster units has become more favourable since it can satisfy the flexible thrust configuration requirements [7][8][9][10][11].…”
Section: Introduction: Microsolid Propellant Thrusters (Mspt)mentioning
confidence: 99%
“…However, KClO 4 prevented the generation of BN. A separate study by Shuji et al [18,19] indicated that KNO 3 promoted the ignition of B-based propellants, both in air and vacuum. Zhang et al [20] reported that even though the ignition characteristics of LiClO 4 were worse than those of The addition of another additive increased the complexity and consistency of B-based propellants [11].…”
mentioning
confidence: 99%